Pollination of Trichosalpinx (Orchidaceae: Pleurothallidinae) by biting midges (Diptera: Ceratopogonidae). (15th March 2018) - BogarÍn, Diego; FernÁndez, Melania; Borkent, Art; Heemskerk, Anton; Pupulin, Franco; RamÍrez, Santiago; Smets, Erik; Gravendeel, Barbara
Abstract: Pleurothallidinae (Epidendreae) are a megadiverse Neotropical orchid subtribe comprising > 5100 species, most of which are probably pollinated by Diptera. The role of pollinators as drivers of species diversity is largely unknown because knowledge of pollination systems in Pleurothallidinae is still scarce. Here, we addressed the pollination of Trichosalpinx s.s . through study of floral anatomy, pollinator behaviour and floral traits shared with other angiosperms to elucidate its pollination mechanisms. We identified midge specimens with DNA barcoding and morphology, documented pollination with video recordings, studied the anatomy of flowers by combining microscopy (light microscopy, scanning electron microscopy and transmission electron microscopy) and histochemistry and analysed floral scents with gas chromatography–mass spectrometry. We found that two Trichosalpinx spp. are pollinated exclusively by female biting midges of a Forcipomyia ( Euprojoannisia ) sp. (Ceratopogonidae). The midges land on the motile lip and appear to suck substances from its papillose surface. We detected secretion of carbohydrates and proteins on the lip and sepals, and thus, Trichosalpinx might stimulate a protein collection instinct in female biting midges. The well-developed mandibles and poorly developed laciniae of the pollinators indicate that they mainly feed on invertebrate hosts from which they draw haemolymph. Thus, Trichosalpinx flowers offer small quantities of proteins and carbohydrates that may act as flavour teases and together with the colour, fragrances, trichomes and movement of the lip, they probably form part of a complex deceptive system. Some other angiosperms that are also pollinated by biting midges possess similar dark purple flowers with ciliate ornamentation and use myophily, sapromyophily or kleptomyiophily as strategies to exploit different families of Diptera as pollinators. One Forcipomyia sp. ( Euprojoannisia ) is kleptoparasitic, suggesting that kleptomyiophily may have evolved in Trichosalpinx . The similar floral morphology among members of Trichosalpinx and some species of the closely related genera Anathallis and Lankesteriana suggests that they are also pollinated by biting midges.